The Categorization of Objects With Uniform Texture at Superordinate and Living/Non-living Levels in Infants: An Exploratory Study - Taniguchi, Kosuke; Tanabe-Ishibashi, Azumi; Itakura, Shoji (Frontiers in Psychology, 2020)
Human infants can categorize objects at various category levels (e.g., as a dog, animal, or living thing). It is crucial to understand how infants learn about the relationships between objects. This study investigated whether 4- to 11-month-old infants can categorize modeled objects at superordinate and living/nonliving levels. In this experiment, we presented modeled objects with a uniform texture constructed by a 3D printer in animal, vegetable/fruit, vehicle, and tool categories and measured the time taken to examine novel categories. We investigated infants’ categorization abilities using familiarization/novelty-preference tasks and their pre-linguistic development based on information from their parents. The analyses examined whether infants dedicated more examination time to objects in the new category at superordinate and living/nonliving levels for each month of age. The results revealed that the examination time among 4- and 5-month-olds was at chance levels for both superordinate and living/nonliving levels, while at 7-months, they showed high preference for the novel category at both category levels. For the superordinate level, the strength of response to living objects increased with linguistic development, while the strength of response to nonliving objects did not depend on linguistic development. This indicates that the superordinate-level categorization of living objects depends on both perceptual information and linguistic ability. For the living/nonliving level, the examination time for nonliving objects increased with linguistic development. This implies that the recognition of nonliving objects may depend on the development of object knowledge. The current study suggests that infants can recognize categories at an abstract level before the acquisition of linguistic representations while the category levels that infants can categorize objects are different for living/nonliving objects. This may imply that infants learn the concepts of living/nonliving via different mechanisms.